Monte Carlo Methods in Finance - Jäckel, Peter (Chichester [etc.] John Wiley & Sons, 2002)
An invaluable resource for quantitative analysts who need to run models that assist in option pricing and risk management. This concise, practical hands on guide to Monte Carlo simulation introduces standard and advanced methods to the increasing complexity of derivatives portfolios. Ranging from pricing more complex derivatives, such as American and Asian options, to measuring Value at Risk, or modelling complex market dynamics, simulation is the only method general enough to capture the complexity and Monte Carlo simulation is the best pricing and risk management method available. The book is packed with numerous examples using real world data and is supplied with a CD to aid in the use of the examples.
Preface Acknowledgements Mathematical Notation Introduction The Mathematics Behind Monte Carlo Methods Stochastic Dynamics Process--driven Sampling Correlation and Co--movement Salvaging a Linear Correlation Matrix Pseudo--random Numbers Low--discrepancy Numbers Non--uniform Variates Variance Reduction Techniques Greeks Monte Carlo in the BGM/J Framework Non--recombining Trees Miscellanea Bibliography Index
Keywords: Matemáticas financieras; Monte Carlo, Método de